Gifted children of color around the world : diverse needs, exemplary practices, and directions for the future - Davis, Joy Lawson, 1953-; Moore, James L., III (Bingley, United Kingdom : Emerald Publishing, 2016)
This edited volume sheds light on the unique challenges, trends, and intersecting issues related to identifying intellectual potential of children of color around the world, providing access to appropriate curriculum and instructional opportunities, addressing the professional capacities of teachers working with these students, and the role of diverse families and communities in the talent development process in these communities.
Gifted education programming: serving the native Peruvian / Sheyla Blumen -- Developing cultural competence in gifted and advanced students using community problem solving / Tarek C. Grantham, Margaret E. Hines, April Dennis, Marianne Solomon, and Brittany N. Anderson -- Si se puede/Yes we can: ramping up efforts for collaborating with Hispanic parents and families / Jaime A. Castellano -- Meeting the academic and socio-emotional needs of twice exceptional African American students through group counseling / Renae D. Mayes, Paul C. Harris and Erik M. Hines -- Talent in every community: a glimpse into the world of parenting gifted children of color / Joy Lawson Davies -- Where are all the Latino males in gifted programs? / Desiree Vega and James L. Moore III -- Teaching to their strengths: good medicine for Native American education / Jerry Lassos and Steven C. Haas -- Biracial and multiracial gifted students: looking for a grain of rice in a box of sand / Donna Y. Ford, Gilman W. Whiting and Ramon B. Goings -- Brief overview of the current state of gifted education in the Dominican Republic / Leticia R. Jaquez, Roman B. Jaquez and D. Socorro Collado -- Gifted children of color in the deep south / Evin d. Besnoy, E. Camille Fears Floyd, Elvira G. Deyamport and Ashley Cavan.
Includes bibliographical references.
Keywords: Gifted children -- Education; Children of minorities -- Education; Children of minorities -- Education; Gifted children -- Education